Physiological responses and transcriptome analysis of soybean under gradual water deficit - Xu, Yuwen; Song, Di; Qi, Xingliang; Asad, Muhammad; Wang, Sui; Tong, Xiaohong; Jiang, Yan; Wang, Shaodong (Frontiers in Plant Science, 2023)
Soybean is an important food and oil crop widely cultivated globally. However, water deficit can seriously affect the yield and quality of soybean. In order to ensure the stability and increase of soybean yield and improve agricultural water use efficiency (WUE), research on improving drought tolerance and the efficiency of water utilization of soybean under drought stress has become particularly important. This study utilized the drought-tolerant variety Heinong 44 (HN44) and the droughtsensitive variety Suinong 14 (SN14) to analyze physiological responses and transcriptome changes during the gradual water deficit at the early seed-filling stage. The results indicated that under drought conditions, HN44 had smaller stomata, higher stomatal density, lower stomatal conductance (Gs) and transpiration rate compared to SN14. Additionally, HN44 had a higher abscisic acid (ABA) content and faster changes in stomatal morphology and Gs to maintain a dynamic balance between net photosynthetic rate (Pn) and Gs. Additionally, drought-tolerant variety HN44 under water deficit had high instantaneous WUE. Further, HN44 retained a high level of superoxide dismutase (SOD) activity and proline content, mitigating malondialdehyde (MDA) accumulation and drought-induced damage. Comprehensive analysis of transcriptomic data revealed that HN44 had fewer differentially expressed genes (DEGs) under light drought stress, reacting insensitivity to water deficit. At the initial stage of drought stress, both varieties had a large number of upregulated DEGs to cope with the drought stress. Under severe drought stress, HN44 had fewer downregulated genes enriched in the photosynthesis pathway than SN14, while it had more upregulated genes enriched in the ABA-mediated signaling and glutathione metabolism pathways than SN14. During gradual water deficit, HN44 demonstrated better drought-tolerant physiological characteristics and water use efficiency than SN14 through key DEGs in the major pathways such as GmbZIP4, LOC100810474, and LOC100819313. Key transcription factors were screened and identified, providing further clarity on the molecular regulatory pathways responsible for the physiological differences in drought tolerance among these varieties. This study deepened the understanding of the drought resistance mechanisms in soybeans, providing valuable references for drought resistance soybean breeding.